Gamified Education Practice: Designing with E-commerce and ilearning Concept - Aini, Qurotul; Budiarto, Mukti; Oktavia, Panca; Putra, Hadi; Santoso, Nuke Puji Lestari; Rahardja6, Untung (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This research discusses two problems that often occur in the learning process in general: first, students often have difficulty understanding, and it is challenging to participate in discussions until then no solution successfully resolves their doubts, and second, the boring e-learning website.Design / methodology / approach: SPSS analysis method using Ms. Excel 2007 and SmartPLS 3.2.8Findings: Therefore, we have a solution to overcome this problem through e-commerce oriented learning practices, as a means for learning to use the Learning Management System.Practical implications: Having a focus on the principles of Analysis and Design of Information Systems, with the concept of computing-oriented e-commerce embedded in the game to motivate the iLearning process.Originality/value: Significance lies in reducing perceptions of gamification and components that are liked or disliked by users and the efficacy of our hybrid approach in system development.